Vasodilator effect of ethanolic extracts of Passiflora vitifolia and Passiflora edulis f. edulis seeds - Ángel Arturo Jiménez Rodríguez&, Jonh Jairo Méndez Arteaga, Walter Murillo Arango, Mario Francisco Guerrero Pabón (Journal of Applied Pharmaceutical Science, 2021)
Hypertension (HTA) is one of the primary risk factors in cardiovascular diseases and is considered one of the main causes of morbidity and mortality worldwide. Therapeutic alternatives focused on natural products and phytocompounds obtain more interest in the treatment of this type of disease, and species of Passiflora gender have presented scientific interest due to their chemical composition and the different bioactivities that their compounds have reported. This study aimed to evaluate the antihypertensive potential of extracts obtained from seeds of Passiflora vitifolia and Passiflora edulis f. edulis; for this, extraction was carried out by maceration with 97% ethanol of the seed flour of the two species; the extracts were characterized by qualitative and quantitative tests and UHPLC. Its cytotoxicity, in vivo antihypertensive potential, vasodilator effect, and possible mechanisms of action in vitro models were evaluated. The extracts did not show apparent toxicity, but showed a preventive effect of HTA, inhibited angiotensin-II (AT-II) contraction, and presented relaxation of contracted aortic rings with phenylephrine and KCl, and this was partially reversed in the presence of L-NAME. The results highlight the potential of these Passifloras as a source of extracts with antihypertensive capacity, having as possible mechanisms of action the synthesis of NO and inhibition or antagonism of AT-II.
Keywords: Bioactive extract, Passiflora, nitric oxide, angiotensin-II, antihypertensives